Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1111/j.1444-0938.2007.00220.x
|View full text |Cite
|
Sign up to set email alerts
|

Glare and halo with refractive correction

Abstract: Background:The aim of this investigation was to compare glare and halo with various methods of refractive correction. Methods: Ninety-eight eyes of healthy pre-presbyopes were analysed for the presence of glare and halo using computer-generated stimuli. Subjects were divided into three groups: emmetropes without correction, single vision plastic lens spectacle wearers (with clean and dirty lenses) or single-vision soft contact lens wearers. Results: No significant difference in glare was found among groups. Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…7,10 Alternatively, the subject had to place a marker at the outer limit of the halo using a computer mouse at a 1 m distance. 13 The main shortcoming of these methods is that if the subject does not see a defi ned halo or does not understand what a halo is, identifi cation of the margin of the halo could be diffi cult. Further, each subject might delimit the halo in a different way.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7,10 Alternatively, the subject had to place a marker at the outer limit of the halo using a computer mouse at a 1 m distance. 13 The main shortcoming of these methods is that if the subject does not see a defi ned halo or does not understand what a halo is, identifi cation of the margin of the halo could be diffi cult. Further, each subject might delimit the halo in a different way.…”
Section: Discussionmentioning
confidence: 99%
“…6 Measuring the size of a glare source-induced halo has been proposed as an objective method of quantifying quality of vision in subjects such as those with night vision problems following refractive surgery, 7,8 with cataract 9 or multifocal intraocular lenses, [10][11][12] and those wearing spectacles or contact lenses. 13 Several methods and testing protocols have been developed to measure halo size. 9,10,13,14 However, methodological limitations such as the subjectivity involved in determining the limit of a diffuse halo on a screen in the absence of a target image with only the glare source makes the fi ndings of such studies diffi cult to interpret.…”
Section: O R I G I N a L A R T I C L Ementioning
confidence: 99%
See 1 more Smart Citation
“…Spectacles alone may induce visual symptoms secondary to factors such as lens refractive index, base curve, and antireflective coatings. 24,25 A secondary aim of this study was to investigate the correlation between preoperative LOCS III grading of cataract with the 10 visual symptoms of the QoV questionnaire frequency subscale. Overall, results indicated no significant correlations between signs and symptoms except for one comparison: posterior subcapsular cataracts were correlated with the visual symptom of blurred vision (r s = 0.420).…”
Section: Commentmentioning
confidence: 99%
“…However, Allen et al (2008) showed that contact lens wearers observe a larger halo around light sources compared to spectacle wearers. Our main interest was to evaluate the changes in visual acuity for myopes depending on the contrast we used for optotypes (standard or reversed) and to see whether the results were affected by the type of optical correction (contact lenses or spectacles).…”
Section: Introductionmentioning
confidence: 99%